HYPOTHESIS TESTING FOR AN EXCHANGEABLE NORMAL DISTRIBUTION (Journal of Sciences, Islamic Republic of Iran)
Consider an exchangeable normal vector with parameters ????2, and ?. On the basis of a vector observation some tests about these parameters are found and their properties are discussed. A simulation study for these tests and a few nonparametric tests are presented. Some advantages and disadvantages of these tests are discussed and a few applications are given.